A New Compensation Control Strategy for Grid-connected Wind Turbine and Fuel Cell Inverters in a Microgrid - A. Naderipour; A. A. Mohd Zin; M. H. Habibuddin; M. Moradi; M. Miveh; H. N. Afrouzi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The use of a new control method for grid-connected inverters for reducing the output current harmonic distortion in a wide range of grid-connected distributed generation (DG) applications, including wind turbine (WT) and fuel cell (FC) inverters is proposed in this paper. The control method designed to eliminate main harmonics in a microgrid (MG) and between MG and point of common coupling (PCC) and responsible for the correction of the system unbalance. Another advantage of the proposed control method is that it can be easily adopted into the DG control system without the installation of extra hardware. The proposed control method is comprised of the synchronous reference frame method (SRF). Results from the proposed control method are provided to show the feasibility of the proposed approach.